Phase-field modeling of coupled bulk photovoltaic effect and ferroelectric domain manipulation at ultrafast timescales - Yi-De Liou; Kena Zhang; Ye Cao (npj Computational Materials)
Abstract The bulk photovoltaic (BPV) effect, which generates steady photocurrents and above-bandgap photovoltages in non-centrosymmetric materials when exposed to light, holds great potential for advancing optoelectronic and photovoltaic technologies. However, its influence on the reconfiguration of ferroelectric domain structure remains underexplored. In this study, we developed a phase-field model to understand the BPV effect in ferroelectric oxides. Our model reveals that variations in BPV currents across domains create opposing charges at domain walls, enhancing the electric field within domains to ~1000 kV/cm. The strong electric fields can reorient the ferroelectric polarization and enable ultrafast domain wall movements and nonvolatile domain switching on the picosecond scale. Applying anisotropic strain can further strengthen this effect, enabling more precise control of domain switching. Our findings advance the fundamental understanding of BPV effect in ferroelectrics, paving the ways for developing opto-ferroelectric memory technologies and high-efficiency photovoltaic applications via precise domain engineering.